A familial disorder associated with palatal myoclonus, other brainstem signs, tetraparesis, ataxia and Rosenthal fibre formation. Issue 9 (September 1993) - Howard, R S; Greenwood, R; Gawler, J; Scaravilli, F; Marsden, C D; Harding, A E
Abstract : Three siblings presented with a progressive neurological disorder beginning in the third decade of life and characterised by palatal myoclonus, nystagmus, bulbar weakness and spastic tetraparesis. There was no evidence of intellectual deterioration or seizures. CT scan showed marked brainstem atrophy in two patients and basal ganglia calcification in one. MRI scan in one showed high signal in the brainstem and periventricular region and cerebral biopsy in this patient showed myelin loss and the presence of Rosenthal fibres. A similar disease affected the siblings' mother, maternal aunt and two of the aunt's daughters, suggesting an autosomal dominant mode of transmission of what appears to be a unique genetic disorder.